Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution